Single-cell transcriptomic profiling reveals specific maturation signatures in human cardiomyocytes derived from LMNB2-inactivated induced pluripotent stem cells - Wang, Jie; Morgan, William; Saini, Ankur; Liu, Tao; Lough, John; Han, Lu (Frontiers in Cell and Developmental Biology, 2022)
Mammalian cardiomyocyte maturation entails phenotypic and functional optimization during the late fetal and postnatal phases of heart development, both processes driven and coordinated by complex gene regulatory networks. Cardiomyocytes derived from human induced pluripotent stem cells (iPSCs) are heterogenous and immature, barely resembling their adult in vivo counterparts. To characterize relevant developmental programs and maturation states during human iPSC-cardiomyocyte differentiation, we performed single-cell transcriptomic sequencing, which revealed six cardiomyocyte subpopulations, whose heterogeneity was defined by cell cycle and maturation states. Two of those subpopulations were characterized by a mature, non-proliferative transcriptional profile. To further investigate the proliferation-maturation transition in cardiomyocytes, we induced loss-of-function of LMNB2, which represses cell cycle progression in primary cardiomyocytes in vivo. This resulted in increased maturation in LMNB2-inactivated cardiomyocytes, characterized by transcriptional profiles related to myofibril structure and energy metabolism. Furthermore, we identified maturation signatures and maturational trajectories unique for control and LMNB2-inactivated cardiomyocytes. By comparing these datasets with single-cell transcriptomes of human fetal hearts, we were able to define spatiotemporal maturation states in human iPSC-cardiomyocytes. Our results provide an integrated approach for comparing in vitro-differentiated cardiomyocytes with their in vivo counterparts and suggest a strategy to promote cardiomyocyte maturation.